INFRARED AND HARD X-RAY DIAGNOSTICS OF ACTIVE GALACTIC NUCLEUS IDENTIFICATION FROM THE SWIFT /BAT AND AKARI ALL-SKY SURVEYS - Matsuta, K.; Gandhi, P.; Dotani, T.; Nakagawa, T.; Isobe, N.; Ueda, Y.; Ichikawa, K.; Terashima, Y.; Oyabu, S.; Yamamura, I.; Stawarz, Ł. (The Astrophysical journal, 2012)
We combine data from two all-sky surveys in order to study the connection between the infrared and hard X-ray (>10 keV) properties for local active galactic nuclei (AGNs). The Swift Burst Alert Telescope all-sky survey provides an unbiased, flux-limited selection of hard X-ray-detected AGNs. Cross-correlating the 22 month hard X-ray survey with the AKARI all-sky survey, we studied 158 AGNs detected by the AKARI instruments. We find a strong correlation for most AGNs between the infrared (9, 18, and 90 mu m) and hard X-ray (14-195 keV) luminosities, and quantify the correlation for various subsamples of AGNs. Partial correlation analysis confirms the intrinsic correlation after removing the redshift contribution. The correlation for radio galaxies has a slope and normalization identical to that for Seyfert 1 galaxies, implying similar hard X-ray/infrared emission processes in both. In contrast, Compton-thick (CT) sources show a large deficit in the hard X-ray band, because high gas column densities diminish even their hard X-ray luminosities. We propose two photometric diagnostics for source classification: one is an X-ray luminosity versus infrared color diagram, in which type 1 radio-loud AGNs are well isolated from the others in the sample. The other uses the X-ray versus infrared color as a useful redshift-independent indicator for identifying CT AGNs. Importantly, CT AGNs and starburst galaxies in composite systems can also be differentiated in this plane based upon their hard X-ray fluxes and dust temperatures. This diagram may be useful as a new indicator to classify objects in new and upcoming surveys such as WISE and NuSTAR.